Enhanced multi-cell coordination in wireless communication system using beamforming methods - Abdulrahman, Omar Khaldoon (School of Computer and Communication Engineering, 2016)
The objectives of this work are as follows to modify and develop new mathematical models of the MVDR algorithm to increase the robustness of MVDR beamformer against steering vector errors caused by calibration or manufacturing errors, and increase the estimation and beamforming accuracy using the actual data mode subjected to double constraints; to design a novel CoMP architecture through innovative division of an LTE cell into three spatial regions, where different scheduling methods (AJN, SCBF, and Non-CoMP) can run in parallel, thus dramatically increasing the capacity of the system; to incorporate MVDR beamformer into CoMP architecture in order to generate accurate beamforming weight within each base station, resulting in reducing signalling overhead among the LTE base stations.